Digitalization of Marketing and Simple Financial Management to Improve the Welfare of MSMEs on the Indonesia-Malaysia Border - Juharsah; Arifuddin; Nurwati; Patwayati; Hamid, Wahyuniati; Aliddin, La Ode Asfahyadin (CV. Literasi Indonesia, 2024)
Digital marketing training and the preparation of simple financial reports are important steps in increasing the capacity of MSMEs on the Indonesia-Malaysia border. The main objective of this activity is to help MSMEs understand and implement digital-based marketing strategies and simple financial management to strengthen business competitiveness. Before the implementation of the activity, the preparation process had been carried out for one month beforehand. This training was conducted using interactive lecture methods, live demos, and practical exercises with 20 MSME participants on Sebatik Island. The results of the training showed an increase in participants' understanding of digital platforms for marketing and the importance of attractive promotional content. Participants also showed enthusiasm in participating in the activities. In addition, simple financial training helped participants recognize the importance of routine financial records to monitor the financial condition of the business. The ability to prepare simple reports such as cash books and a basic understanding of digital financial applications began to be applied by participants. Based on these results, it is proposed that there be a sustainable mentoring program to support the implementation of consistent digital marketing strategies and financial management for MSMEs on the border. With the sustainability of mentoring, it is hoped that MSMEs can optimize their potential, increase market access, and strengthen local economic stability in border areas.